INTENTION TO USE DIGITAL PAYMENT DURING THE COVID-19 PANDEMIC IN THE RURAL AREA - Sutresna, I Kadek; Safira, Nabila; Kartono, Rano (Jurnal Ilmiah Manajemen, Ekonomi, & Akuntansi (MEA), 2023)
A cashless society and technical progress are now more widely accepted. The widespread covid-19 epidemic, which coincided with the creation of formal financial services globally, has significantly increased digital payment. Even in a pandemic, the use of digital payment may be discovered to be different if segregated by geography. There is a significant disparity in financial inclusion between urban and rural areas. This study will look at people's intentions to use digital payment during the covid-19 pandemic. This research will continue to learn about the intention to utilize digital payment in rural communities in West Java, Indonesia. This study is based on quantitative data. The survey was carried out using online questionnaires. The information was gathered from 225 digital payment consumers in rural West Java, Indonesia. SEM-PLS is used in this study. Statistical analysis software that works with SMART-PLS4. Our findings reveal that users in rural areas prefer digital payments due to performance expectations and social influence. People in rural areas do not use digital payments for health reasons, such as fears of contracting covid-19, as reflected by perceived severity and susceptibility.